East-West literary relations - Dasgupta, R. K. (Rabindra Kumar) (Calcutta, India : Papyrus Publishing, 1995)
On Indic English literature and its comparison with Western literature.
Includes bibliographical references.
Keywords: Indic literature (English) -- 20th century -- History and criticism; Comparative literature -- Indic and Western; Comparative literature -- Western and Indic